2017
DOI: 10.1111/evo.13159
|View full text |Cite
|
Sign up to set email alerts
|

Song evolution, speciation, and vocal learning in passerine birds

Abstract: Phenotypic divergence can promote reproductive isolation and speciation, suggesting a possible link between rates of phenotypic evolution and the tempo of speciation at multiple evolutionary scales. To date, most macroevolutionary studies of diversification have focused on morphological traits, whereas behavioral traitsincluding vocal signalsare rarely considered. Thus, although behavioral traits often mediate mate choice and gene flow, we have a limited understanding of how behavioral evolution contributes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
99
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 124 publications
5
99
1
Order By: Relevance
“…More recently, Mason et al. () found that body size was more important than habitat in the evolution of song in tanagers (Thraupidae), but no information was available regarding beak size. Thus, we still have only a limited understanding of the relative roles of these mechanisms, partly because comprehensive information on phylogenetic relationships, signal design, morphology, and ecology are rarely available for large radiations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Mason et al. () found that body size was more important than habitat in the evolution of song in tanagers (Thraupidae), but no information was available regarding beak size. Thus, we still have only a limited understanding of the relative roles of these mechanisms, partly because comprehensive information on phylogenetic relationships, signal design, morphology, and ecology are rarely available for large radiations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in common with other tracheophone suboscine passerines (Tobias & Seddon, ; Tobias et al., ; Touchton, Seddon, & Tobias, ), their songs appear to be innate with song learning limited or absent. This minimizes the effect of cultural processes on song evolution (Mason et al., ; Weir & Wheatcroft, ) and means that ovenbird songs are relatively simple and amenable to acoustic analysis (Tobias et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Relative to the accumulation of novel genetic markers or other traits, behavioral evolution via exchange of learned song can be rapid (Allender, Seehausen, Knight, Turner, & Maclean, ; Duckworth, ; West‐Eberhard, ). Further, species that learn their song evolve new dialects particularly quickly (Mason et al, ; but see Freeman, Montgomery, & Schluter, ). Rapid evolution of songs could mediate and/or supplement divergences across the Cochise Filter Barrier.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, song evolves over time as it passes through generations. Evolutionary biologist Elizabeth Derryberry of the University of Tennessee, Knoxville, and Nicholas Mason, a doctoral candidate in ecology and evolutionary biology at Cornell University, studied two families of birds: the tanagers (Thraupidae) that learn song and the ovenbirds (Furnariidae) that are innate singers (12). What they found suggests that culture could play a sizeable role.…”
Section: Speciation and Songmentioning
confidence: 99%
“…Derryberry and Mason (12) acknowledge that they don't know whether bird song evolution drives speciation or vice versa. In one scenario, bird song could diverge first, which would prevent individuals with different songs from mating together, setting their lineages on the path to becoming distinct species.…”
Section: Speciation and Songmentioning
confidence: 99%